2013
DOI: 10.4103/2156-7514.112799
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Adenocarcinoma of the Minor Salivary Glands Involving Palate and Maxillary Sinus

Abstract: Basal cell adenocarcinoma (BCAC) is a rare neoplasm accounting for only 2.9% of all salivary gland neoplasms. BCAC involving palatal minor salivary glands are exceedingly rare, and only 10 cases have been reported in the literature. The treatment of choice is surgical excision. Here, we report a case of a 55-year-old male patient with massive BCAC of palatal minor salivary gland extending into the maxillary sinus. This is the first case of BCAC treated by radiotherapy followed by chemotherapy. A follow-up chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Nadir görülen bazal hücreli adenokarsinomu tükrük bezinin diğer bazaloid tümörlerinden ayırt etmek prognoz ve tedavideki farklılıklar nedeniyle önemlidir. Bazal hücreli adenomdan ayırt etmek zor olmakla birlikte bizim olgumuzda olduğu gibi esas olarak çevre yapılara invazyon ya da perinöral, vasküler invazyonun saptanması tanı koydurur (5). Polimorfoz düşük dereceli adenokarsinom, bazaloid tip skuamöz hücreli karsinom, küçük hücreli karsinom, ameloblastomun bazaloid varyantı ayırıcı tanıya giren diğer tümörlerdir (2).…”
Section: Olgu Sunumuunclassified
See 1 more Smart Citation
“…Nadir görülen bazal hücreli adenokarsinomu tükrük bezinin diğer bazaloid tümörlerinden ayırt etmek prognoz ve tedavideki farklılıklar nedeniyle önemlidir. Bazal hücreli adenomdan ayırt etmek zor olmakla birlikte bizim olgumuzda olduğu gibi esas olarak çevre yapılara invazyon ya da perinöral, vasküler invazyonun saptanması tanı koydurur (5). Polimorfoz düşük dereceli adenokarsinom, bazaloid tip skuamöz hücreli karsinom, küçük hücreli karsinom, ameloblastomun bazaloid varyantı ayırıcı tanıya giren diğer tümörlerdir (2).…”
Section: Olgu Sunumuunclassified
“…Olgu Sunumu Case Report büyüme paterni ile maligniteyi işaret eden epitelyal neoplazi' olarak tanımlamıştır (4). Bazal hücreli adenomun malign versiyonu olduğu da düşünülmektedir (5).…”
unclassified
“…After 4 weeks, she experienced 50% reduction in nodal size, which remained stable at subsequent monthly visits. 3 Sarath et al 16 reported a patient with a massive, inoperable, maxillary BCAC who was favorably treated with radiation followed by chemotherapy. The authors reported no local recurrence or metastases at 14-month follow-up.…”
Section: Treatmentmentioning
confidence: 99%
“…Its synonyms include carcinoma ex-monomorphic adenoma, basaloid salivary gland carcinoma, and malignant basal cell tumor. 2 At the time of this writing, no large population-level studies of major salivary BCAC exist, with the majority of BCAC literature being individual case reports or small case series, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] the largest of which is 27 patients by Ellis and Wiskovitch (1990). 17 The National Cancer Database (NCDB) is the largest cancer registry in the world, capturing 70% of all cancer diagnoses in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Its synonyms include carcinoma ex‐monomorphic adenoma, basaloid salivary gland carcinoma, and malignant basal cell tumor . At the time of this writing, no large population‐level studies of major salivary BCAC exist, with the majority of BCAC literature being individual case reports or small case series, the largest of which is 27 patients by Ellis and Wiskovitch (1990) …”
Section: Introductionmentioning
confidence: 99%